Highly Porous Cu2O Photocathode via Electrochemical Reconstruction of Dense Thin Films. Issue 3 (11th March 2021) - Singh, Akhilender Jeet; Aggarwal, Garima; Das, Chandan; Balasubramaniam, K. R.
Abstract : Nanostructured light absorbers in PEC devices offer enhanced charge carrier collection and increased active area compared to planar structures. This article describes a simple two-step electrochemical treatment to obtain such nanostructured films of Cu2 O absorber layer. A dense Cu2 O film is electrodeposited on FTO coated glass substrate at a potential of −0.35 V (vs Ag/AgCl). This precursor film is then subjected to voltage cycling in a potential range of −0.6 V to 0.6 V, resulting in reconstruction of the top 0.5 μ m dense film to 10–30 nm thick nano-walled structure. The reason for this reconstruction is a concomitant etching of Cu2 O as Cu 2+ ions along with oxidation to CuO. A morphology preserving reduction of the porous CuO during the cathodic scan results in a nano-walled Cu2 O. From linear sweep voltammetry of pristine Cu2 O and CuO films, we find that reduction of Cu2 O to Cu is a slow process in this potential range and hence, Cu-impurity is not observed up to 50 cycles. Such an approach offers production of phase pure nanostructured films comprising features as small as 10 nm without following any complex procedure. The reconstructed porous Cu2 O shows > 50% enhancement in photocurrent over dense Cu2 O.